Spermatogenesis and spermatozoal ultrastructure in Metapenaeus monoceros (Fabricius, 1798) - Abraham, Joice; Manissery, Mary K; Sanil, N K (Indian Journal of Fisheries, 2011)
Spermatogenesis in the ‘speckled shrimp’ Metapenaeus monoceros (Fabricius,1798) was studied employing histological and transmission electron microscopictechniques. Male specimens of the species were classified into three maturitystages based on gross morphology. Spermatozoa of M. monoceros was observedto be unistellate with a spherical main body and a spike. The main body wasmade up of a central nuclear region, a peripheral cytoplasmic band and anacrosomal cap, which overlaid the nuclear region anteriorly. From the acrosomalcap projected an extended spike towards the anterior of the spermatozoa. Thespike and the acrosomal cap together were called the acrosomal vesicle. Theaverage length of the spermatozoa was 6μ m. The main body had a mean diameterof 3.4μ m with the spike measuring 2.6μ m in length.